New perspectives from the bicentennial - Sobrevilla Perea, Natalia (2021)
In this edition of the magazine From the South we find a series of reflections on Peru framed within the commemoration of the bicentennial. Although only one of them focuses on directly studying the period of independence, and its analysis does not focus on how the separation with Spain was achieved or on the celebrations held in these years of pandemic, it is clear that all of the Papers in this issue contribute to the understanding of Peru in this specific context. 2021 has been a particular year. On the one hand, the country and the entire world are still immersed in the complex and changing reality of the pandemic, while, on the other hand, Peru has lived through an intense and exhausting electoral process that has not managed to put an end to the political instability that It has characterized it for the last five years.